Initial response of autistic children in human-robot interaction therapy with humanoid robot NAO - Shamsuddin, Syamimi; Yussof, Hanafiah; Ismail, Luthffi; Hanapiah, Fazah Akhtar; Mohamed, Salina; Ali Piah, Hanizah; Zahari, Nur Ismarrubie
The overall context proposed in this paper is part of our long-standing goal to contribute to a group of community that suffers from Autism Spectrum Disorder (ASD); a lifelong developmental disability. The objective of this paper is to present the development of our pilot experiment protocol where children with ASD will be exposed to the humanoid robot NAO. This fully programmable humanoid offers an ideal research platform for human-robot interaction (HRI). This study serves as the platform for fundamental investigation to observe the initial response and behavior of the children in the said environment. The system utilizes external cameras, besides the robot’s own visual system. Anticipated results are the real initial response and reaction of ASD children during the HRI with the humanoid robot. This shall leads to adaptation of new procedures in ASD therapy based on HRI, especially for a non-technical-expert person to be involved in the robotics intervention during the therapy session.